PENGARUH KELENGKAPAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Swalayan Ada Baru Di Kota Salatiga) - Widodo, Tri (AMONG MAKARTI, 2016)
AbstractCompleteness of the product for a self-service meruapakan important factor to attract consumers. The more complete product offered more it will meet the desires and needs of consumers. In addition to a range of products, quality of service is also a key to the success of efforts to develop usahaanya sebauh. Thus providing good service becomes important. Completeness of product and service quality as a whole will be a consideration and will influence consumer purchase decisions in the purchase of products needed. So that the range of products and quality of service, had to be considered Supermarkets Adabaru in an effort to attract consumers and create a customer. This study design is the design of a survey conducted in order to test the effect of Completeness of product and service quality of the buying decision at Supermarket Adabaru Salatiga. Survey conducted on 96 respondents who are consumers Supermarkets Adabaru Salatiga.Data analysis was performed using multiple linear regression. The results showed that: 1) Based on the questionnaire respondents Supermarkets Adabaru completeness of the product does not significantly influence the purchasing decision; 2) Quality of care significantly influence the purchasing decisions of consumers; 3) Completeness of product and service quality simultaneously significantly influence the purchasing decisions in Supermarkets Adabaru. Keywords : Completeness of Product, Service Quality, Purchasing Decisions